Boomerang ecosystem fluxes: organic carbon inputs from land to lakes are returned to terrestrial food webs via aquatic insects. Issue 12 (4th June 2014) - Scharnweber, K.; Vanni, M. J.; Hilt, S.; Syväranta, J.; Mehner, T.
<x xml:space="preserve">Abstract</x> Many ecosystems are linked to their adjacent ecosystems by movements of organisms. For instance, aquatic and terrestrial ecosystems are linked via emerging aquatic insects that serve as prey for terrestrial consumers. However, the role of these organisms in returning recycled carbon to the ecosystem from which it originated is not well known. This is due to the fact that values of carbon isotope signatures from terrestrial leaves and aquatic resources are usually similar and hence results of isotope mixing models need to be considered with caution. We overcame this problem by adding isotopically distinct terrestrial particulate organic carbon (tPOC) as a tracer to the experimental sides of two lakes that were divided in two equal halves with plastic curtains. We focused on aquatic insect larvae (Chironomidae) that fed on maize Zea mays leaves experimentally added to the lakes, and subsequently became prey for terrestrial predators (spiders) after emergence. The carbon isotope values of Chironomidae and spiders were significantly elevated in the lake treatment sides as compared to reference sides, whereas the values of all autochthonous resources were not affected by maize additions. Estimates from stable isotope mixing models indicated a low but demonstrable contribution of maize leaves to the diet of Chironomidae. Overlap between the isotope values of alder leaves, the major natural tPOC source, and autochthonous resources prevented a reliable quantification of allochthony of Chironomidae. However, we qualitatively demonstrated the flow of terrestrial particulate organic carbon to lakes, as leaf fall, and back to terrestrial surroundings via emerging insects. This 'boomerang' carbon flux between land and lakes blurs the distinction between autochthonous and allochthonous carbon sources.